2021
DOI: 10.3390/antiox10030493
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Pregnancy and Exposure to Tobacco Smoke on Blood Antioxidant Status and Copper, Zinc, Cadmium Concentration—A Pilot Study

Abstract: The aim of the study was to evaluate the impact of early pregnancy and exposure to tobacco smoke on antioxidant status and copper, zinc, and cadmium concentrations in the blood of non-smoking and smoking, as well as non-pregnant or pregnant women. The study included 213 women. More specifically, 150 women in first trimester of pregnancy and 63 non-pregnant women. Women were divided into subgroups according to exposure to tobacco smoke. Pregnancy significant influences higher copper and lower zinc concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
(79 reference statements)
1
11
1
Order By: Relevance
“…To the best of our knowledge, this is the first report to describe the effect of smoke on oxidized glutathione levels in the blood of pregnant women, which in the physiological stage accounts for less than 1–2% of the total GSH pool and increases under conditions of oxidative stress [ 15 , 17 ]. We observed higher levels of GSSG and slightly higher levels of GPx in smokers compared with non-smokers, while other authors showed significantly higher activity of this enzyme [ 9 , 19 , 20 ]. These differences may be due to the fact that we determined the level of an extracellular form of glutathione peroxidase (GPx-3), which is most abundant in plasma, while others tested total GPx activity [ 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first report to describe the effect of smoke on oxidized glutathione levels in the blood of pregnant women, which in the physiological stage accounts for less than 1–2% of the total GSH pool and increases under conditions of oxidative stress [ 15 , 17 ]. We observed higher levels of GSSG and slightly higher levels of GPx in smokers compared with non-smokers, while other authors showed significantly higher activity of this enzyme [ 9 , 19 , 20 ]. These differences may be due to the fact that we determined the level of an extracellular form of glutathione peroxidase (GPx-3), which is most abundant in plasma, while others tested total GPx activity [ 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 57%
“…In pregnant tobacco smokers, maintaining redox homeostasis seems to be particularly important in the context of the well-being of both mother and child [ 9 , 10 ]. Tobacco smoke contains a number of toxic compounds, including oxidants and FRs, which are responsible for the intensification of oxidative stress and the occurrence of pathological changes in the body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations